JEJAK BAHASA JAWA SAMIN KLOPODUWUR BLORA (Sebuah Rekaman Sinkronis) - Eva Ardiana Indrariani (Universitas PGRI Semarang, 2013)
Linguists noted people in the region Blora have unique Javanese tradition still maintained until now,namely